Address by Dr Manmohan Singh Hon’ble Prime Minister of India - Planning Commission (Planning Commission, 2006)
I am very pleased to be here today to inaugurate this conference on the challenges and opportunities of building infrastructure in India. The theme of this conference is extremely relevant to the economic future of our nation and I believe that it will afford an opportunity for a wide range of participants to appreciate the challenges and opportunities in India’s infrastructure sectors. India’s economic performance in the past few years - particularly in the last three years - has been commendable on many counts. Economic growth has accelerated and we are now averaging an annual growth in excess of 8%. A fascinating story is unfolding and the entire world is watching with wonder the emergence of India as a major economic force. However, this growth has not been without limitations. Many marginalised sections of society and large segments of the farming community have not benefited from this growth process. We need a faster and more inclusive growth process. Both objectives present challenges, but both are achievable through sustained effort. Our government is investing intensively in the social and welfare sectors so as to improve the capabilities of our people to make them active participants in the evolving growth story.
Planning Commission Government of India
Planning Commission Government of India